Prices in the Transition : Ten Stylized Facts - De Masi, Paula (IMF Working Papers; Working Paper, 1997)
The overall price level increased sharply in transition countries once prices were freed. Disinflation has most frequently been gradual, with prices continuing to rise rapidly in subsequent years. This paper identifies the well-known and lesser-known features of inflationary processes in central and eastern Europe, the Baltics, Russia, and other countries of the former Soviet Union on the basis of a sample of 26 countries and observations spanning the first five to seven years of transition.